Contravention of regulatory provisions in public procurement to the common rules of the Administrative General Procedure Law Single Ordered Text - Rojas Vásquez, Piero (2020)
The Single Ordered Text (hereinafter, “TUO”) of the General Administrative Procedure Law (hereinafter, “LPAG”) is, at the moment, classified as a common standard. This qualification implies that the special administrative procedures, indicated both in law or regulation, cannot deviate from the rules and principles established in the same TUO of the LPAG. Hence, based on the above-mentioned premise, this article aims to demonstrate that there are provisions of the sanction administrative procedure regime drafted in public contract regulations that manifestly contravene the common standard previously described.